2012
DOI: 10.1016/j.jpba.2012.07.023
|View full text |Cite
|
Sign up to set email alerts
|

A 96-well filtration method for radioligand binding analysis of σ receptor ligands

Abstract: σ Receptors represent a potential drug target for numerous therapeutic indications including cancer, depression, psychostimulant abuse, and stroke. Most published radioligand binding studies for σ receptors utilize a low throughput method employing a “cell harvester.” Higher throughput methods are required to facilitate efficient screening of large numbers of novel compounds. In this study, a series of reference compounds was analyzed with a new medium-throughput 96-well filtration method and the results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…This interpretation would be consistent with other reports of multiple regions for ligand interactions on the σ 1 receptor, some of which have functional ramifications for agonist vs. antagonist activity [35], [36], [37]. The affinity differences of dextromethorphan for its two putative binding sites appear to be similar (<100-fold difference) since competition binding assays of dextromethorphan at σ 1 receptors are consistent with a one-site fit [27]. The antidepressant-like effects of dextromethorphan are thought to be mediated through the competitive binding site since i) there appears to be a rightward shift in its dose response curve in the forced swim test with no apparent change in maximal effect, and ii) (+)-pentazocine, the σ 1 agonist used to label the receptor, has previously also been reported to produce similar antidepressant-like effects [10], [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This interpretation would be consistent with other reports of multiple regions for ligand interactions on the σ 1 receptor, some of which have functional ramifications for agonist vs. antagonist activity [35], [36], [37]. The affinity differences of dextromethorphan for its two putative binding sites appear to be similar (<100-fold difference) since competition binding assays of dextromethorphan at σ 1 receptors are consistent with a one-site fit [27]. The antidepressant-like effects of dextromethorphan are thought to be mediated through the competitive binding site since i) there appears to be a rightward shift in its dose response curve in the forced swim test with no apparent change in maximal effect, and ii) (+)-pentazocine, the σ 1 agonist used to label the receptor, has previously also been reported to produce similar antidepressant-like effects [10], [17].…”
Section: Discussionsupporting
confidence: 90%
“…The concentration of dextromethorphan used in these assays was based on the reported K i of the drug for σ 1 receptors [27]. Briefly, 15 concentrations of [ 3 H](+)-pentazocine (0.1–100 nM) were used to label σ 1 receptors in P 2 rat brain homogenates (400–500 µg/sample).…”
Section: Methodsmentioning
confidence: 99%
“…This interpretation would be consistent with other reports of multiple regions for ligand interactions on the sigma-1 receptor, some of which have functional ramifications for agonist vs. antagonist activity (Cobos et al, 2005;Wu and Bowen, 2008;Yamamoto et al, 1999). The affinity differences of DM for its two putative binding sites appear to be similar (<100-fold difference) since competition binding assays of DM at sigma-1 receptors are consistent with a one-site fit (Fishback et al, 2012). The antidepressant-like effects of DM are thought to be mediated through the competitive binding site since i) there appears to be a rightward shift in its dose response curve in the FST with no apparent change in maximal effect, and ii) (+)-pentazocine, the sigma-1 receptor agonist used to label the receptor, has previously also been reported to produce similar antidepressant-like effects (Fishback et al, 2010;Matsuno et al, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…Earlier competition binding studies showed that DM has significant affinity for sigma-1 receptors (138-652 nM) (Chou et al, 1999;Fishback et al, 2012;Nam et al, 2012;Werling et al, 2007b), and thus further characterization of the interaction of DM with sigma-1 receptors was undertaken in the current study. The saturation binding studies indicate that the interaction of DM with sigma-1 receptors is complex, with both a change in Bmax and Kd in the binding of Together, the data support the presence of at least two distinct sites or modes of interaction with which DM binds to the sigma-1 receptor, one with which it has competitive interactions, and another with which it has non-competitive interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A library of benzo[ d ]thiazol-2( 3H )one analogues were synthesized and their receptor binding affinities were evaluated in rat liver membranes using a 96 well format high throughput methodology. 25 The −1 receptors were labeled with 5nM [ 3 H](+)-pentazocine. The −2 receptors were labeled with 5 nM [ 3 H]DTG in the presence of 300 nM (+)-pentazocine.…”
mentioning
confidence: 99%